A Handful of Details to Ensure the Experimental Reproducibility on the FORCED Running Wheel in Rodents: A Systematic Review - Garrigos, Daniel; Martínez-Morga, Marta; Toval, Angel; Kutsenko, Yevheniy; Barreda, Alberto; Do Couto, Bruno Ribeiro; Navarro-Mateu, Fernando; Ferran, José Luis (Frontiers in Endocrinology, 2021)
A well-documented method and experimental design are essential to ensure the reproducibility and reliability in animal research. Experimental studies using exercise programs in animal models have experienced an exponential increase in the last decades. Complete reporting of forced wheel and treadmill exercise protocols would help to ensure the reproducibility of training programs. However, forced exercise programs are characterized by a poorly detailed methodology. Also, current guidelines do not cover the minimum data that must be included in published works to reproduce training programs. For this reason, we have carried out a systematic review to determine the reproducibility of training programs and experimental designs of published research in rodents using a forced wheel system. Having determined that most of the studies were not detailed enough to be reproducible, we have suggested guidelines for animal research using FORCED exercise wheels, which could also be applicable to any form of forced exercise.